Analisis Korelasional Sistem Informasi Manajemen dengan Efektivitas Kerja Pegawai - Fientje Palijama; La Jaali (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
This study aims to analyze the relationship of the management system to the effectiveness of employee work at the office of the BPM-PD Kabupten Kepulauan Aru. This type of research is classified as explanatory research. The population of this study is all BPM-PD supervisors of Aru Islands Regency and the sampling technique used is a census technique so that the entire population is sampled in this study. Research data collection using questionnaire instruments distributed online via google form to all respondents. The analysis tool used is correlation analysis or product moment. The results prove that management information systems have a low relationship with work effectiveness.